Growth‐Oriented Fe‐Based MOFs Synergized with Graphene Aerogels for High‐Performance Supercapacitors. Issue 8 (8th February 2018) - Liu, Lin; Yan, Yang; Cai, Zihe; Lin, Shengxuan; Hu, Xiaobin
Abstract: Metal–organic frameworks (MOFs) and graphene aerogels (GAs) are both considered as good candidates for high‐performance supercapacitors. In this work, a growth‐oriented Fe‐based MOF synergized with GA composite for supercapacitor is prepared. MIL‐88‐Fe is in situ grown at (002) lattice plane on the surface of graphene via a one‐step solvothermal method. Long periodic hexagonal structure and electrophilicity of MOF provide strong p–π interaction with graphene sheets. By utilizing the abundant interspace of GA, the existence of MOF could affect the electric double‐layer characteristics of composites. The MOF/GA composites have the advantages of high capacitive volume, fast charge/discharge rate, and reliable cycling stability. The specific capacitance is as high as 353 F g −1 at the scan rate of 20 A g −1, and the retention ratio is 74.4% after 10 000 cycles. Abstract : Growth‐oriented, rod‐like MIL‐88‐Fe is synthesized on the surface of graphene via one‐step solvothermal method, which immensely enhances the electrochemical performances for supercapacitors. The results point to the possibility of using metal–organic framework and functionalized graphene to prepare high‐performance electrode with high capacitive volume, fast charge/discharge rate, and reliable cycling stability.